Two-Dimensional TiO2 Ultraviolet Filters for Sunscreens - Yang, Ruoning; Chen, Jiefu; Li, Xiang; Zhang, Yaxin; Ding, Baofu; Xu, Yujiangsheng; Luo, Shaoqiang; Ma, Shaohua; Ren, Xingang; Liu, Gang; Qiu, Ling; Cheng, Hui‑Ming (Nano-Micro Letters, 2025)
Titanium dioxide (TiO2) has been an important protective ingredient in mineral-based sunscreens since the 1990s. However, traditional TiO2 nanoparticle formulations have seen little improvement over the past decades and continue to face persistent challenges related to light transmission, biosafety, and visual appearance. Here, we report the discovery of two-dimensional (2D) TiO2, characterized by a micro-sized lateral dimension (~1.6 μm) and atomic-scale thickness, which fundamentally resolves these long-standing issues. The 2D structure enables exceptional light management, achieving 80% visible light transparency—rendering it nearly invisible on the skin—while maintaining UV-blocking performance comparable to unmodified rutile TiO2 nanoparticles. Its larger lateral size results in a two-orders-of-magnitude reduction in skin penetration (0.96 w/w%), significantly enhancing biosafety. Moreover, the unique layered architecture inherently suppresses the generation of reactive oxygen species (ROS) under sunlight exposure, reducing the ROS generation rate by 50-fold compared to traditional TiO2 nanoparticles. Through precise metal element modulation, we further developed the first customizable sunscreen material capable of tuning UV protection ranges and automatically matching diverse skin tones. The 2D TiO2 offers a potentially transformative approach to modern sunscreen formulation, combining superior UV protection, enhanced safety and a natural appearance. Highlights: 1 Two-dimensional (2D) TiO2 was developed with > 99% visible light transmittance for non-whitening UV protection, outperforming conventional 0D TiO2 in aesthetics while matching UV-blocking efficacy. 2 2D TiO2 achieves ultralow skin penetration and 90% reduced reactive oxygen species generation versus 0D TiO2, eliminating photocatalytic toxicity and DNA damage risks. 3 2D TiO2 enabled tunable UVA/UVB coverage via metal doping without compromising visible light transmittance, ensuring Scientific Committee on Consumer Safety compliance and biocompatibility. 4 We integrated high UV protection, natural appearance, and photoinertness into a single material, redefining aesthetic-safe sunscreen design through 2D structural innovation.